The riddle of the sands : a record of secret service - Childers, Erskine, 1870-1922. (London : Vintage Books, 2013)
Two young Englishmen set off on a leisurely sailing holiday in the period before the first World War; however, their lives are threatened after an encounter with a mysterious German yachtsman and his daughter off the North Sea coast of Germany.
Adult.
Adult
Keywords: Sailing -- Fiction; Secret service -- Fiction; Adventure fiction; Alternative histories; Sailing -- Fiction; Sea stories; Secret service -- Fiction; Spy stories; Frisian Islands -- Fiction; Great Britain -- History -- Invasions -- Fiction; Frisian Islands -- Fiction; Great Britain -- History -- Fiction; Adventure fiction; Alternative histories (Fiction); Sea stories; Spy stories